Secular trends of epidemiologic patterns of chronic kidney disease over three decades: an updated analysis of the Global Burden of Disease Study 2019 - Jing Liu; Xue Li; Yongping Liu; Xiaodong Sun; Xiaojin Feng; Ningning Hou; Zhenna Chen (BMJ Open)
Objectives To assess the characteristics of the global death burden imposed by chronic kidney disease (CKD) and the attributable risk factors from 1990 to 2019 to help inform a framework for policy discussions, resource allocation and research priorities.Design A population-based observational study.Setting The death data and relative risk factors were obtained from the Global Burden of Disease (GBD) Study 2019 database.Main outcome measures Based on the GBD database, we estimated the death burden attributable to CKD stratified by sociodemographic index (SDI), geographic location, sex, age group, time period and risk factors from 1990 to 2019.Results Over three decade study period, the global number of CKD-related deaths increased from 0.60 million (95% uncertainty interval (UI): 0.57–0.63 million) in 1990 to 1.43 million (95% UI: 1.31–1.52 million) in 2019. The age-standardised death rate (ASDR) of CKD, among all causes, increased from 15th in 1990 to 10th in 2019. Globally, the ASDR in males was higher than that in females. CKD-related deaths mainly occurred in those aged over 50 years, especially in regions with higher SDIs. The ASDR was negatively related to SDI (ρ=−0.603, p<0.0001). Among risk factors, metabolic risk factors, especially systolic blood pressure, fasting plasma glucose and body mass index, were the main contributors to CKD-related deaths. Although the high-temperature-related death burden was low, the trend increased sharply in lower SDI regions.Conclusions CKD-related deaths continue to increase, with the majority occurring in elderly adults. The CKD-related death burden is higher in males than in females. Additionally, the increasing high-temperature-related death burdens in lower SDI regions should receive social attention.